2022
DOI: 10.20944/preprints202203.0326.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the Effect of Consumers’ Knowledge on their Acceptance of Functional Foods: A Systematic Review and Meta-Analysis

Abstract: Inconsistent results published in previous studies make it difficult to determine the precise effect of consumer knowledge on their acceptance of functional foods, which were developed to improve consumers’ health status by providing adequate nutrition. We conducted a systematic review and meta-analysis by identifying and collecting relevant literature from three databases. Of the 1050 studies we reviewed, we included 40 in the systematic review and 18 in meta-analysis. Based on the focus of each inc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 69 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…When it comes to awareness level it was observed that there exist three categories of consumer knowledge which are: i) knowledge of the concept of functional foods (i.e., knowledge of the definition of functional food and functional food description), ii) nutritional knowledge associated with consuming functional foods (i.e., knowledge about nutrition, diet-related issues and health claims), and iii) specific functional food products' knowledge (i.e., knowledge about specific functional foods, functional ingredients, functional foods brands) [8]. In another study it was found that the knowledge about micronutrient deficiencies and the availability of fortified staple foods is low in India and along with it the study revealed that although the awareness and consumption of fortified food was found low but the males were found to have good awareness and the source of information gain was family members, peers, internet and media [9].…”
Section: Review Of Literaturementioning
confidence: 99%
“…When it comes to awareness level it was observed that there exist three categories of consumer knowledge which are: i) knowledge of the concept of functional foods (i.e., knowledge of the definition of functional food and functional food description), ii) nutritional knowledge associated with consuming functional foods (i.e., knowledge about nutrition, diet-related issues and health claims), and iii) specific functional food products' knowledge (i.e., knowledge about specific functional foods, functional ingredients, functional foods brands) [8]. In another study it was found that the knowledge about micronutrient deficiencies and the availability of fortified staple foods is low in India and along with it the study revealed that although the awareness and consumption of fortified food was found low but the males were found to have good awareness and the source of information gain was family members, peers, internet and media [9].…”
Section: Review Of Literaturementioning
confidence: 99%